The Regional Dimension of the Waste Management in Volyn and Rivne Regions (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article examines the state of the waste management in Volyn and Rivne regions. It is shown the presence of the major polluters in areas, analyzed degreeof utilization and the share of waste as secondary raw materials. Also was taken into account the experience of Japan in the recycling resources and regional features of Volyn and Rivne regions.Proposed directions of intensification of providing secondary resources in these areas.
Keywords: waste, secondary resources, landfills, utilization, recycling, mercury cleaning process